The Influence Of Gemu Famire Gymnastics On Early Childrhoods's Rhythmic Movement Ability In Kampong Bharu Guidance Center, Kuala Lumpur, Malaysia - Yuli Sawitri; Desti Pujiati (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2023)
Rhythmic movement ability is an essential component in the motor development of early childhood. It contains elements of flexibility, rhythm, movement accuracy, and continuous movement. The lack of stimulation and the lack of focus on developing motor skills, especially rhythmic movements, makes it difficult for some children to move according to the rhythm and coordinate the movements of their hands and feet. One effort that can be done is to use rhythmic gymnastics. This study aimed to determine the effect of Gemu Famire Gymnastics on the ability of early childhood rhythmic movements in the Kampong Bharu Guidance Center. The type of research used was experimental research with a pretest–posttest control group design. Samples were taken from pre-GC children with an age range of 5 - 7 years with 20 children (10 children in the experimentclass and 10 children in the control class). Data were collected using observation and then processed and analyzed using the t-test. Based on the  analysis results, the data results are normally distributed with the same variance value. Then, based on the results of testing the hypothesis with the t-test, the t count  score = 2.653 and t table 2.100 were obtained. If the two were compared, it can be concluded that t count t table, which means that Gemu Famire gymnastics affected the ability of early childhood rhythmic movements at the Kampong Bharu Guidance Center, Kuala Lumpur, Malaysia.